2007
DOI: 10.1002/jmri.20984
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative magnetization transfer imaging in postmortem multiple sclerosis brain

Abstract: Purpose: To investigate the relationship of myelin content, axonal density, and gliosis with the fraction of macromolecular protons (f B ) and T 2 relaxation of the macromolecular pool (T 2B ) acquired using quantitative magnetization transfer (qMT) MRI in postmortem brains of subjects with multiple sclerosis (MS). Conclusion: f B in MS WM is dependent on myelin content and may be a tool to monitor patients with this condition. Materials and Methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
297
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 252 publications
(310 citation statements)
references
References 55 publications
6
297
0
Order By: Relevance
“…They concluded that both techniques are sufficiently suited to detect microstructural tissue alterations at least in the white matter of the murine brain. Postmortem histological analyses assessing myelin content, axonal density, and gliosis revealed similar correlations in brains of patients with Alzheimer's disease [29] or multiple sclerosis [71][72][73].…”
Section: Age-related White Matter Changes and Normal-appearing Brain mentioning
confidence: 71%
See 1 more Smart Citation
“…They concluded that both techniques are sufficiently suited to detect microstructural tissue alterations at least in the white matter of the murine brain. Postmortem histological analyses assessing myelin content, axonal density, and gliosis revealed similar correlations in brains of patients with Alzheimer's disease [29] or multiple sclerosis [71][72][73].…”
Section: Age-related White Matter Changes and Normal-appearing Brain mentioning
confidence: 71%
“…As can also be seen from Table 4 in vivo studies in humans consistently reported that mean diffusivity and fractional anisotropy, and in most investigations also magnetization transfer ratios, are more affected in agerelated white matter lesions than in normal-appearing white matter [7,22,43,59,69,72,81]. There existed a significant association between white matter lesion load and severity of DTI and MTR measures in the normalappearing white matter with the microstructural changes in normal brain tissue being more closely related to the patients' clinical presentation than the volume of visible white matter abnormalities [9,32,52,61,69,70,74,92,93].…”
Section: Age-related White Matter Changes and Normal-appearing Brain mentioning
confidence: 73%
“…PET ligands targeting the 18 kDa translocator protein, which is upregulated with inflammation, detect neuroinflammation in human diseases including multiple sclerosis and in animal models, but the effectiveness of these PET markers remains to be seen (Banati et al, 2000;Papadopoulos et al, 2006;Chauveau et al, 2009Chauveau et al, , 2011Abourbeh et al, 2012;Xie et al, 2012). Promising advances in imaging myelination have been reported including myelin water imaging (MacKay et al, 1994;Du et al, 2007;Laule et al, 2008;Hwang et al, 2010;Prasloski et al, 2012), magnetization transfer (Inglese et al, 2003;Schmierer et al, 2004Schmierer et al, , 2007aDortch et al, 2011;Stikov et al, 2011;Underhill et al, 2011), optical imaging (Wang et al, 2011a) and myelin-specific PET markers (Wang et al, 2009;Wu et al, 2013). For specifically identifying axon injury and loss, reduced NAA content measured by magnetic resonance spectroscopy (MRS) has been used (De Stefano et al, 1999;Aboul-Enein et al, 2010;Wood et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Currently available quantitative MRI techniques have been validated using standard histology (Mottershead et al, 2003;Schmierer et al, 2003Schmierer et al, , 2004Schmierer et al, , 2007aFisniku et al, 2009). However, a rigorously quantitative validation of magnetic resonance pathologic metrics has been relatively limited in part due to the difficulty to co-register quantitative histology findings with MRI.…”
Section: Discussionmentioning
confidence: 99%
“…Separating the fundamental parameters of the two-pool model requires an additional measurement of the "long" observed T 1 (T 1obs ), from which the free pool R 1f can then be computed (6). The MWF, MT ratio, and certain QMTI parameters have respectively been shown to correlate with myelin content and demyelination (11)(12)(13).…”
mentioning
confidence: 99%